Preparation method of double-layer polypyrrole deposition foam nickel sodium alginate hydrogel solar evaporator

By adopting a double-layer polypyrrole deposition foam nickel sodium alginate hydrogel structure in a solar interface evaporator, the problem of reducing evaporation rate caused by the accumulation of evaporation surface salt is solved, and efficient seawater evaporation and photothermal conversion are achieved, and good stability and environmental protection performance.

CN119191429AActive Publication Date: 2024-12-27HEILONGJIANG UNIV

Patent Information

Application Number
CN202411559183.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2024-12-27
Estimated Expiration
2044-11-04

AI Technical Summary

Technical Problem

The accumulation of evaporation surface salt in existing solar interface evaporators will reduce the evaporation rate of the evaporator and affect its long-term stability.

Method used

The structure of foam nickel foamed nickel alginate is deposited by double-layer polypyrrole, and the foamed nickel foamed by electrodepositing as the absorbing layer and the sodium alginate hydrogel as the water absorption layer is formed to form an upper and lower structure, and the double-health of polypyrrole is used to effectively use it. Solar energy absorption is converted into thermal energy and increases hydrophilicity through the hydroxyl and carboxylic groups of sodium alginate and accelerates moisture transport through micron-scale channels.

Benefits of technology

The optimal evaporation rate of seawater is 3.22Kg·m-2·h-1 and the photothermal efficiency is 91.8%, which improves the evaporation rate and photothermal conversion efficiency of the evaporator, and has good anti-salt deposition ability and environmentally friendly biological phase. Capacity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119191429A_ABST
    Figure CN119191429A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a double-layer polypyrrole deposition foam nickel sodium alginate hydrogel solar evaporator, and belongs to the field of preparation of solar evaporators. The invention aims to solve the problems that the evaporation rate of the evaporator is reduced and the long-term stability of the evaporator is influenced due to salt accumulation on the evaporation surface of the existing solar interface evaporator. The method comprises the following steps: 1, preparing a foamed nickel light absorption layer of electro-deposition polypyrrole; 2, preparing a sodium alginate hydrogel; and 3, combining the water absorption layer and the light absorption layer to prepare the solar seawater evaporation system. The preparation method is used for preparing the double-layer polypyrrole deposition foam nickel sodium alginate hydrogel solar evaporator.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of solar evaporator preparation. Background Art

[0002] With the depletion of fresh water resources, people are increasingly looking for new technologies to obtain fresh water resources. Seawater desalination is one of the most promising technologies. Traditional seawater desalination technologies include reverse osmosis, multi-stage flash evaporation and electrodialysis, but they have some disadvantages, such as difficult equipment and process, high energy consumption, and environmental pollution. In recent years, solar thermal driven interfacial evaporation technology has become a hot topic. It combines solar thermal technology with water delivery structure, concentrates heat energy on the evaporation surface, reduces losses, improves evaporation efficiency, and has the advantages of sustainability and high energy efficiency.

[0003] High-performance solar-driven interface evaporator water treatment systems need to select suitable water-absorbing materials and design a reasonable structure to transport water to the solar absorber through capillary force to form a thin water layer. The photothermal component needs to absorb enough light energy and convert it into heat energy to evaporate the thin water layer. However, the accumulation of salt on the evaporation surface of the existing solar interface evaporator will reduce the evaporation rate of the evaporator and affect the long-term stability of the evaporator. Summary of the invention

[0004] The present invention aims to solve the problem that salt accumulation on the evaporation surface of the existing solar interface evaporator will reduce the evaporation rate of the evaporator and affect the long-term stability of the evaporator, and further provide a preparation method of a double-layer polypyrrole deposited nickel foam sodium alginate hydrogel solar evaporator.

[0005] A method for preparing a double-layer polypyrrole deposited nickel foam sodium alginate hydrogel solar evaporator is carried out according to the following steps:

[0006] 1. Preparation of nickel foam light-absorbing layer of electrodeposited polypyrrole:

[0007] ① washing and drying the nickel foam to obtain pretreated nickel foam;

[0008] ② mixing pyrrole, acetonitrile and tetrabutylammonium tetrafluoroborate to obtain a mixed solution of pyrrole, acetonitrile and tetrabutylammonium tetrafluoroborate;

[0009] ③ Using the pretreated nickel foam as the working electrode, the copper sheet as the counter electrode, silver chloride as the reference electrode, and the mixed solution of pyrrole, acetonitrile and tetrabutylammonium tetrafluoroborate as the electrodeposition solution, the electrochemical workstation uses the chronoamperometry method, and the electrodeposition is performed for 1000s to 2000s at a voltage of 1V to 4V and a temperature of 20°C to 50°C. After deposition, the nickel foam light-absorbing layer of the electrodeposited polypyrrole is washed and dried.

[0010] 2. Preparation of sodium alginate hydrogel:

[0011] ① Add sodium alginate into distilled water to obtain a sodium alginate solution;

[0012] ② Add calcium chloride to distilled water to obtain a calcium chloride solution;

[0013] ③ Adding calcium chloride solution into sodium alginate solution and heating to dissolve to obtain sodium alginate hydrogel;

[0014] 3. Combining water absorption layer and light absorption layer to prepare solar seawater evaporation system:

[0015] The electro-deposited polypyrrole nickel foam light-absorbing layer is placed at the bottom of a container, and the sodium alginate hydrogel is poured into the container from the surface of the electro-deposited polypyrrole nickel foam light-absorbing layer to form a hydrogel layer on the upper surface of the electro-deposited polypyrrole nickel foam light-absorbing layer, and then the container is allowed to stand for one time at room temperature until bubbles in the hydrogel are discharged, and a calcium chloride solution is added to the hydrogel layer along the inner wall of the container, and then the container is allowed to stand for a second time at room temperature, and the sample is taken out and soaked in distilled water, and finally the excess hydrogel is removed to obtain a double-layer polypyrrole deposited nickel foam sodium alginate hydrogel solar evaporator;

[0016] The double-layer polypyrrole deposited nickel foam and sodium alginate hydrogel solar evaporator is a top-bottom structure, the nickel foam of the electrodeposited polypyrrole is a light absorbing layer, and the sodium alginate hydrogel is a water absorbing layer.

[0017] The beneficial effects of the present invention are:

[0018] The method for preparing a double-layer polypyrrole deposition nickel foam sodium alginate hydrogel solar evaporator provided by the present invention calculates the polypyrrole deposition thickness in the light absorbing layer, the sodium alginate content and the calcium chloride content in the water absorbing layer, and the optimal evaporation rate of the prepared double-layer evaporator acting on seawater is 3.22 kg·m -2 ·h -1 , the photothermal efficiency is 91.8%, proving that the double-layer structure has a higher evaporation rate and photothermal conversion efficiency.

[0019] When the double-layer structure is prepared by the present invention, since the electro-deposited polypyrrole nickel foam light-absorbing layer is immersed in the hydrogel, the hydrogel layer formed on the side and bottom of the nickel foam needs to be removed, so that the double-layer polypyrrole deposited nickel foam sodium alginate hydrogel solar evaporator is finally made into an upper and lower structure, the electro-deposited polypyrrole nickel foam is the light-absorbing layer, and the sodium alginate hydrogel is the water-absorbing layer; the thickness of the hydrogel layer formed on the surface is different, and the evaporation rate of the evaporator will be different to a certain extent.

[0020] When preparing the sodium alginate hydrogel in the evaporator of the present invention, calcium chloride is added twice. The first time it is added during the heating and dissolution process of the sodium alginate, it can be evenly distributed in the sodium alginate hydrogel by heating and stirring; the second time it is added after the sodium alginate hydrogel is allowed to stand, and it is soaked in a calcium chloride solution to cross-link the calcium ions with the gel. Adding calcium chloride in batches helps the calcium ions to gradually penetrate into the entire sodium alginate gel. If a large amount of calcium ions are added at one time, it will cause the local calcium ion concentration to be too high, causing the cross-linking reaction to proceed rapidly in some locations, while the sodium alginate in other locations may not be fully cross-linked due to insufficient diffusion of calcium ions. Adding calcium chloride twice for gradual cross-linking helps to form a more uniform three-dimensional network structure, which can avoid certain areas from being too soft or too hard, thereby improving the strength and toughness of the hydrogel as a whole.

[0021] The double-layer polypyrrole deposited nickel foam sodium alginate hydrogel solar evaporator prepared by the present invention has an upper layer of a nickel foam light-absorbing layer and a lower layer of a sodium alginate hydrogel water-absorbing layer. Polypyrrole contains a large number of double bonds that can effectively absorb solar energy and convert it into heat energy for water evaporation. Sodium alginate has a large number of hydroxyl and carboxyl groups that increase hydrophilicity. Micron-scale pores accelerate water transport and ensure the wettability of the evaporation surface.

[0022] The invention is simple to operate and can be mass-produced; the prepared double-layer polypyrrole deposited on the nickel foam sodium alginate hydrogel solar evaporator consumes less energy, has sufficient strength and is convenient to use.

[0023] Instruction Manual

[0024] Figure 1 1 is a spectrum of RTIR, 1 is sodium alginate hydrogel, 2 is polypyrrole prepared in step 1 of Example 1;

[0025] Figure 2 UV-visible-near infrared spectrum and AM1.5G spectrum solar radiation spectrum of the double-layer polypyrrole deposited nickel foam sodium alginate hydrogel solar evaporator and sodium alginate hydrogel prepared in Example 1;

[0026] Figure 3 1 is a SEM image of a nickel foam and a nickel foam light-absorbing layer of electrodeposited polypyrrole, a is the nickel foam described in step 1 ① of embodiment 1, and b is the nickel foam light-absorbing layer of electrodeposited polypyrrole prepared in step 1 ③ of embodiment 1;

[0027] Figure 4 is the SEM image of sodium alginate hydrogel;

[0028] Figure 5 This is the contact angle test diagram of sodium alginate hydrogel;

[0029] Figure 6 For 1kw / m 2The surface temperature test diagram of the light-absorbing layer of the double-layer polypyrrole electrodeposited nickel foam sodium alginate hydrogel solar evaporator prepared in Example 1 under light intensity;

[0030] Figure 7 When the solar intensity is 1kw / m 2 The relationship between the evaporation rate and photothermal efficiency of the double-layer polypyrrole deposited nickel foam sodium alginate hydrogel solar evaporator prepared in Examples 1 to 5 and the concentration change of calcium chloride in the sodium alginate hydrogel in step 2③ under room temperature conditions;

[0031] Figure 8 When the solar intensity is 1kw / m 2 and the relationship between the evaporation rate, photothermal efficiency and hydrogel thickness of the double-layer polypyrrole deposited nickel foam sodium alginate hydrogel solar evaporator prepared in Examples 3, 6 to 9 under room temperature conditions;

[0032] Fig. 9 When the solar intensity is 1kw / m 2 And under room temperature conditions, the evaporation rate diagram of the double-layer polypyrrole deposited nickel foam sodium alginate hydrogel solar evaporator prepared in Example 1 in NaCl solutions of different concentrations for 8 hours;

[0033] Fig.10 When the solar intensity is 1kw / m 2 Under room temperature conditions, the evaporation rate variation diagram of the double-layer polypyrrole electrodeposited nickel foam sodium alginate hydrogel solar evaporator prepared in Example 1 was repeatedly evaporated in 25% NaCl solution for 7 days;

[0034] Fig.11 When the solar intensity is 1kw / m 2 A comparison of pH test papers before and after evaporation of 1 mol / L HCL and 1 mol / L NaOH solutions using the double-layer polypyrrole deposited nickel foam sodium alginate hydrogel solar evaporator prepared in Example 1 under room temperature conditions;

[0035] Fig.12 This is a physical picture of the double-layer polypyrrole deposited nickel foam sodium alginate hydrogel solar evaporator prepared in Example 1. DETAILED DESCRIPTION

[0036] Specific implementation method 1: This implementation method is a preparation method of a double-layer polypyrrole deposited nickel foam sodium alginate hydrogel solar evaporator, which is carried out according to the following steps:

[0037] 1. Preparation of nickel foam light-absorbing layer of electrodeposited polypyrrole:

[0038] ① washing and drying the nickel foam to obtain pretreated nickel foam;

[0039] ② mixing pyrrole, acetonitrile and tetrabutylammonium tetrafluoroborate to obtain a mixed solution of pyrrole, acetonitrile and tetrabutylammonium tetrafluoroborate;

[0040] ③ Using the pretreated nickel foam as the working electrode, the copper sheet as the counter electrode, silver chloride as the reference electrode, and the mixed solution of pyrrole, acetonitrile and tetrabutylammonium tetrafluoroborate as the electrodeposition solution, the electrochemical workstation uses the chronoamperometry method, and the electrodeposition is performed for 1000s to 2000s at a voltage of 1V to 4V and a temperature of 20°C to 50°C. After deposition, the nickel foam light-absorbing layer of the electrodeposited polypyrrole is washed and dried.

[0041] 2. Preparation of sodium alginate hydrogel:

[0042] ① Add sodium alginate into distilled water to obtain a sodium alginate solution;

[0043] ② Add calcium chloride to distilled water to obtain a calcium chloride solution;

[0044] ③ Adding calcium chloride solution into sodium alginate solution and heating to dissolve to obtain sodium alginate hydrogel;

[0045] 3. Combining water absorption layer and light absorption layer to prepare solar seawater evaporation system:

[0046] The electro-deposited polypyrrole nickel foam light-absorbing layer is placed at the bottom of a container, and the sodium alginate hydrogel is poured into the container from the surface of the electro-deposited polypyrrole nickel foam light-absorbing layer to form a hydrogel layer on the upper surface of the electro-deposited polypyrrole nickel foam light-absorbing layer, and then the container is allowed to stand for one time at room temperature until bubbles in the hydrogel are discharged, and a calcium chloride solution is added to the hydrogel layer along the inner wall of the container, and then the container is allowed to stand for a second time at room temperature, and the sample is taken out and soaked in distilled water, and finally the excess hydrogel is removed to obtain a double-layer polypyrrole deposited nickel foam sodium alginate hydrogel solar evaporator;

[0047] The double-layer polypyrrole deposited nickel foam and sodium alginate hydrogel solar evaporator is a top-bottom structure, the nickel foam of the electrodeposited polypyrrole is a light absorbing layer, and the sodium alginate hydrogel is a water absorbing layer.

[0048] The polypyrrole prepared in step 1 of this specific embodiment is a conjugated conductive polymer with good light absorption performance. Its broadband light absorption characteristics can effectively absorb the spectral range from ultraviolet to near infrared. Depositing it on nickel foam can significantly improve the photothermal conversion efficiency of the material. The electrodeposition technology can accurately control the thickness and deposition speed of polypyrrole, and can adjust the light absorption efficiency and thermal conductivity of the material. This controllability enables the performance of polypyrrole nickel foam material to be optimized according to application requirements.

[0049] In step 2 of this specific embodiment, sodium alginate has strong ionic cross-linking ability and good mechanical strength. Sodium alginate can be cross-linked with divalent Ca 2+Cross-linking quickly forms a stable gel structure, and the formed gel has good mechanical stability and durability in environmental changes. Salt deposition resistance: Compared with other natural or synthetic hydrogels, sodium alginate hydrogel has better salt deposition resistance in high-salt environments, making it more suitable for seawater evaporation purification applications. Environmental protection and biocompatibility: Sodium alginate is a natural polymer derived from seaweed with good biocompatibility and degradability. When used in seawater purification systems, it is harmless to the environment and is easily degraded or recycled in later treatments, meeting environmental protection requirements.

[0050] In step three of this specific implementation method, the water molecules in the hydrogel network can be divided into three types: water molecules adjacent to the polymer chain connected by hydrogen bonds are called bound water, intermediate water with weak hydrogen bonds to the polymer chain, and free water not constrained by the polymer chain. The evaporation enthalpy of the intermediate water is lower than that of bound water and free water, so that the evaporation enthalpy of water in the hydrogel material is lower than that of pure water.

[0051] The beneficial effects of this implementation are:

[0052] The method for preparing a double-layer polypyrrole deposited nickel foam sodium alginate hydrogel solar evaporator provided in this embodiment is to calculate the polypyrrole deposition thickness in the light absorbing layer, the sodium alginate content and the calcium chloride content in the water absorbing layer, and the optimal evaporation rate of the prepared double-layer evaporator acting on seawater is 3.22 kg·m -2 ·h -1 , the photothermal efficiency is 91.8%, proving that the double-layer structure has a higher evaporation rate and photothermal conversion efficiency.

[0053] When preparing a double-layer structure in this embodiment, since the electro-deposited polypyrrole nickel foam light-absorbing layer is immersed in the hydrogel, it is necessary to remove the hydrogel layer formed on the side and bottom of the nickel foam, so that the double-layer polypyrrole deposited nickel foam sodium alginate hydrogel solar evaporator is finally made into an upper and lower structure, in which the electro-deposited polypyrrole nickel foam is the light-absorbing layer and the sodium alginate hydrogel is the water-absorbing layer; the thickness of the hydrogel layer formed on its surface is different, and the evaporation rate of the evaporator will be different to a certain extent.

[0054] In the present embodiment, calcium chloride is added twice when preparing sodium alginate hydrogel in the evaporator. The first time it is added during the heating and dissolution process of sodium alginate, and it can be evenly distributed in the sodium alginate hydrogel by heating and stirring; the second time it is added after the sodium alginate hydrogel is allowed to stand, and it is soaked in calcium chloride solution to cross-link the calcium ions with the gel. Adding calcium chloride in batches helps the calcium ions to gradually penetrate into the entire sodium alginate gel. If a large amount of calcium ions are added at one time, the local calcium ion concentration will be too high, causing the cross-linking reaction to proceed rapidly in some locations, while the sodium alginate in other locations may not be fully cross-linked due to insufficient diffusion of calcium ions. Adding calcium chloride twice for gradual cross-linking helps to form a more uniform three-dimensional network structure, which can avoid certain areas being too soft or too hard, thereby improving the strength and toughness of the hydrogel as a whole.

[0055] The upper layer of the double-layer polypyrrole deposited nickel foam sodium alginate hydrogel solar evaporator prepared in this embodiment is a nickel foam light-absorbing layer, and the lower layer is a sodium alginate hydrogel water-absorbing layer. Polypyrrole contains a large number of double bonds that can effectively absorb solar energy and convert it into heat energy for water evaporation. Sodium alginate has a large number of hydroxyl and carboxyl groups, which increase the hydrophilicity. The micron-scale pores accelerate water transport and ensure the wettability of the evaporation surface.

[0056] The present embodiment is simple to operate and can be mass-produced; the obtained double-layer polypyrrole deposited on nickel foam sodium alginate hydrogel solar evaporator consumes less energy, has sufficient strength, and is easy to use.

[0057] Specific implementation method 2: This implementation method is different from the specific implementation method 1 in that the thickness of the nickel foam described in step 1① is 1 mm to 5 mm, and the porosity is 80% to 98%. The rest is the same as the specific implementation method 1.

[0058] Specific embodiment 3: This embodiment differs from specific embodiment 1 or 2 in that: the volume ratio of pyrrole to acetonitrile in step 1 ② is 1:(100-200); the mass ratio of the volume of pyrrole to tetrabutylammonium tetrafluoroborate in step 1 ② is 1 mL:(1-3) g. The rest is the same as specific embodiment 1 or 2.

[0059] Specific implementation method 4: This implementation method is different from specific implementation methods 1 to 3 in that the distance between the working electrode and the counter electrode in step 1 ③ is 2 cm to 3 cm. The rest is the same as specific implementation methods 1 to 3.

[0060] Specific implementation method 5: This implementation method is different from specific implementation methods 1 to 4 in that the mass percentage of the sodium alginate solution in step 2① is 2.5% to 4.5%; the mass percentage of the calcium chloride solution in step 2② is 0.15% to 0.30%. Other aspects are the same as specific implementation methods 1 to 4.

[0061] Specific implementation method 6: This implementation method is different from specific implementation methods 1 to 5 in that the volume ratio of the calcium chloride solution to the sodium alginate solution in step 2 ③ is 1:(1.5-3). Other aspects are the same as specific implementation methods 1 to 5.

[0062] Specific embodiment 7: This embodiment is different from Specific embodiments 1 to 6 in that the heating and dissolving in step 2③ is carried out at a temperature of 80°C to 90°C for 45min to 90min. The rest is the same as Specific embodiments 1 to 6.

[0063] Specific implementation eight: This implementation differs from specific implementations one to seven in that: in step three, the first step is to stand at room temperature for 0.5h to 1.5h; in step three, the second step is to stand at room temperature for 15h to 24h; in step three, the step is to soak in distilled water at room temperature for 4h to 12h. The rest is the same as specific implementations one to seven.

[0064] Specific embodiment 9: This embodiment differs from Specific embodiments 1 to 8 in that: in step 3, a hydrogel layer with a thickness of 1 cm to 3 cm is formed on the upper surface of the electro-deposited polypyrrole nickel foam light-absorbing layer; the mass percentage of the calcium chloride solution in step 3 is 0.05% to 0.1%. The rest is the same as Specific embodiments 1 to 8.

[0065] Specific embodiment 10: This embodiment differs from Specific embodiments 1 to 9 in that the volume ratio of the calcium chloride solution in step 3 to the sodium alginate hydrogel added to the container is 1:(0.5-2). Other aspects are the same as Specific embodiments 1 to 9.

[0066] The following examples are used to verify the beneficial effects of the present invention:

[0067] Embodiment 1:

[0068] A method for preparing a double-layer polypyrrole deposited nickel foam sodium alginate hydrogel solar evaporator is carried out according to the following steps:

[0069] 1. Preparation of nickel foam light-absorbing layer of electrodeposited polypyrrole:

[0070] ① Wash the nickel foam with distilled water and ethanol in turn, and then dry it at 70°C for 10 minutes to obtain the pretreated nickel foam;

[0071] The nickel foam has an area of ​​3×3 cm, a thickness of 1.7 mm, and a porosity of 95%;

[0072] ② Mix 0.5 mL of pyrrole, 60 mL of acetonitrile and 0.85 g of tetrabutylammonium tetrafluoroborate to obtain a mixed solution of pyrrole, acetonitrile and tetrabutylammonium tetrafluoroborate;

[0073] ③ The pretreated nickel foam was used as the working electrode, the copper sheet was used as the counter electrode, the silver chloride was used as the reference electrode, the mixed solution of pyrrole, acetonitrile and tetrabutylammonium tetrafluoroborate was used as the electrodeposition solution, and the electrochemical workstation selected the chronoamperometry method. Under the conditions of voltage of 2V and temperature of 25°C, the electrodeposition was performed for 1000s. After deposition, it was washed with water and ethanol and dried at a temperature of 70°C to obtain the nickel foam light-absorbing layer of electrodeposited polypyrrole;

[0074] The copper sheet has an area of ​​3×3 cm and a thickness of 1.7 mm; the distance between the working electrode and the counter electrode is 2 cm;

[0075] 2. Preparation of sodium alginate hydrogel:

[0076] ① Add 1.2 g of sodium alginate into 40 mL of distilled water to obtain a sodium alginate solution;

[0077] ② Add 0.042 calcium chloride to 20 mL of distilled water to obtain a calcium chloride solution;

[0078] ③ Add 20 mL of calcium chloride solution to 40 mL of sodium alginate solution, and heat to dissolve at 85° C. for 1 h to obtain a sodium alginate hydrogel; the concentration of calcium chloride in the sodium alginate hydrogel is 0.07 w / v%;

[0079] 3. Combining water absorption layer and light absorption layer to prepare solar seawater evaporation system:

[0080] The electro-deposited nickel foam light-absorbing layer of polypyrrole is placed at the bottom of the container, and the sodium alginate hydrogel is poured into the container from the surface of the electro-deposited nickel foam light-absorbing layer of polypyrrole, and a hydrogel layer with a thickness of 2 cm is formed on the upper surface of the electro-deposited nickel foam light-absorbing layer of polypyrrole, and then the layer is allowed to stand for 1 hour at room temperature, and a calcium chloride solution is added to the hydrogel layer along the inner wall of the container, and then the layer is allowed to stand for 16 hours at room temperature for a second time, and the sample is taken out and soaked in distilled water for 6 hours, and finally the excess hydrogel is removed to obtain a double-layer polypyrrole-deposited nickel foam sodium alginate hydrogel solar evaporator;

[0081] The mass percentage of the calcium chloride solution is 0.5%; the volume ratio of the calcium chloride solution to the sodium alginate hydrogel added to the container is 1:1; the double-layer polypyrrole deposited nickel foam sodium alginate hydrogel solar evaporator is an upper and lower structure, the electrodeposited polypyrrole nickel foam is a light absorbing layer, and the sodium alginate hydrogel is a water absorbing layer.

[0082] In the preparation process of step three of this embodiment, nickel foam is immersed in hydrogel. Finally, the hydrogel layer formed on the side and bottom of the nickel foam needs to be removed, so that the double-layer polypyrrole deposited nickel foam and sodium alginate hydrogel solar evaporator is an upper and lower structure, the nickel foam of electrodeposited polypyrrole is the light absorbing layer, and the sodium alginate hydrogel is the water absorbing layer.

[0083] Example 2: This example is different from Example 1 in that: in step 2②, 0.030 calcium chloride is added to 20 mL of distilled water to obtain a calcium chloride solution; in step 2③, the concentration of calcium chloride in the sodium alginate hydrogel is 0.05 w / v%. The rest is the same as Example 1.

[0084] Example 3: This example is different from Example 1 in that: in step 2②, 0.036 calcium chloride is added to 20 mL of distilled water to obtain a calcium chloride solution; in step 2③, the concentration of calcium chloride in the sodium alginate hydrogel is 0.06 w / v%. The rest is the same as Example 1.

[0085] Example 4: This example differs from Example 1 in that: in step 2②, 0.048 calcium chloride is added to 20 mL of distilled water to obtain a calcium chloride solution; in step 2③, the concentration of calcium chloride in the sodium alginate hydrogel is 0.08 w / v%. The rest is the same as Example 1.

[0086] Example 5: This example differs from Example 1 in that: in step 2②, 0.054 calcium chloride is added to 20 mL of distilled water to obtain a calcium chloride solution; in step 2③, the concentration of calcium chloride in the sodium alginate hydrogel is 0.09 w / v%. The rest is the same as Example 1.

[0087] Example 6: This example is different from Example 1 in that the sodium alginate hydrogel is poured into the container from the surface of the electro-deposited polypyrrole nickel foam light absorbing layer, and a hydrogel layer with a thickness of 3 cm is formed on the upper surface of the electro-deposited polypyrrole nickel foam light absorbing layer. The rest is the same as Example 1.

[0088] Embodiment 7: This embodiment is different from Embodiment 1 in that the sodium alginate hydrogel is poured into the container from the surface of the electro-deposited polypyrrole nickel foam light absorbing layer, and a hydrogel layer with a thickness of 2.5 cm is formed on the upper surface of the electro-deposited polypyrrole nickel foam light absorbing layer. The rest is the same as Embodiment 1.

[0089] Embodiment 8: This embodiment is different from Embodiment 1 in that the sodium alginate hydrogel is poured into the container from the surface of the electro-deposited polypyrrole nickel foam light absorbing layer, and a hydrogel layer with a thickness of 1.5 cm is formed on the upper surface of the electro-deposited polypyrrole nickel foam light absorbing layer. The rest is the same as Embodiment 1.

[0090] Embodiment 9: This embodiment is different from Embodiment 1 in that the sodium alginate hydrogel is poured into the container from the surface of the electro-deposited polypyrrole nickel foam light absorbing layer, and a hydrogel layer with a thickness of 1 cm is formed on the upper surface of the electro-deposited polypyrrole nickel foam light absorbing layer. The rest is the same as Embodiment 1.

[0091] Comparative Experiment 1: The difference between this embodiment and the embodiment 1 is that in step 3, the nickel foam light-absorbing layer of the electrodeposited polypyrrole is placed at the bottom of the container and put into the mold, the sodium alginate hydrogel is poured into the container from the surface of the nickel foam light-absorbing layer of the electrodeposited polypyrrole, and a hydrogel layer with a thickness of 2 cm is formed on the upper surface of the nickel foam light-absorbing layer of the electrodeposited polypyrrole, and due to the control of the mold, half of the nickel foam is immersed in the hydrogel, and half of the nickel foam is not immersed in the hydrogel, and finally the excess hydrogel is removed. The rest is the same as the embodiment 1.

[0092] Comparative Experiment 2: The difference between this embodiment and the embodiment 1 is that the sodium alginate hydrogel prepared in step 2 is poured into a container, left to stand for 1 hour at room temperature, then the calcium chloride solution is added to the hydrogel layer along the inner wall of the container, then left to stand for 16 hours at room temperature for a second time, the sample is taken out and soaked in distilled water for 6 hours, and then the electrodeposited polypyrrole nickel foam prepared in step 1 is placed on the surface of the hydrogel with a thickness of 2 cm, to obtain a solar evaporator in which the nickel foam is not completely immersed in the sodium alginate hydrogel. The rest is the same as the embodiment 1.

[0093] Figure 1 , 2 The sodium alginate hydrogels described in , 4 and 5 are all prepared according to the following steps: pour the sodium alginate hydrogel prepared in step 2 of Example 1 into a container, let it stand at room temperature for 1 hour, then add the calcium chloride solution into the hydrogel layer along the inner wall of the container, then let it stand for a second time at room temperature for 16 hours, take out the sample and soak it in distilled water for 6 hours to obtain the sodium alginate hydrogel; the mass percentage of the calcium chloride solution is 0.5%; the volume ratio of the calcium chloride solution to the sodium alginate hydrogel added to the container is 1:1.

[0094] The nickel foam part of the nickel foam light-absorbing layer of the electrodeposited polypyrrole prepared in step 1 of Example 1 was removed, and the remaining polypyrrole was subjected to RTIR test; Figure 1 1 is the spectrum of RTIR, 1 is sodium alginate hydrogel, 2 is the polypyrrole prepared in step 1 of Example 1; it can be seen from the figure that in the spectrum of sodium alginate hydrogel, the -1 is the stretching vibration of OH, located at 1621 and 1423 cm -1 They are C=O asymmetric and symmetric stretching vibrations, indicating the successful solidification of sodium alginate and calcium ions; in the polypyrrole spectrum, the two vibrations are located at 1545 and 1461 cm -1 The C=C stretching and CN stretching of the pyrrole ring are located at 1042 and 902 cm-1 It is the vibration in the CH plane and the deformation of the CH ring, which shows that polypyrrole was successfully synthesized.

[0095] Figure 2 The UV-Vis-NIR spectrum and AM1.5G spectrum solar radiation spectrum of the double-layer polypyrrole deposited nickel foam sodium alginate hydrogel solar evaporator and the sodium alginate hydrogel prepared in Example 1; the absorbance test within the wavelength range of 300-2500nm observed that the absorbance of the sodium alginate hydrogel itself was relatively low, below 15%. In comparison, due to the presence of the light-absorbing material electrodeposited polypyrrole, the absorbance of the evaporator within the wavelength range of 300-2500nm was significantly improved, reaching 94%-99%.

[0096] Figure 3 The SEM images of nickel foam and nickel foam light-absorbing layer of electrodeposited polypyrrole are shown in Figure 1. a is the nickel foam described in step 1 ① of Example 1, and b is the nickel foam light-absorbing layer of electrodeposited polypyrrole prepared in step 1 ③ of Example 1. As can be seen from the figure, the original nickel foam exhibits a rich void structure, and after polypyrrole is electrodeposited on the surface, large interconnected voids are still maintained.

[0097] Figure 4 This is the SEM image of sodium alginate hydrogel; as can be seen from the figure, the sodium alginate hydrogel contains many microporous channels, which supply water to the upper layer of light-absorbing substances.

[0098] Figure 5 This is the contact angle test diagram of sodium alginate hydrogel; it can be seen from the figure that a 10uL water droplet on the surface can be quickly absorbed within 0.1s, indicating that sodium alginate hydrogel has strong water absorption. There are a large number of hydrophilic groups in the sodium alginate chain, which quickly transport water to the evaporation interface during evaporation.

[0099] Figure 6 For 1kw / m 2 The surface temperature test diagram of the light absorption layer of the double-layer polypyrrole electrodeposited nickel foam sodium alginate hydrogel solar evaporator prepared in Example 1 under light intensity; the surface temperature at 0, 5, 10, 20, 40, and 60 minutes was recorded using an infrared camera. It was observed that the initial surface temperature in the evaporator was 24°C, reaching 42°C after 20 minutes of irradiation, and the temperature was stable at 42°C within 60 minutes, indicating that the absorption of heat energy and the consumption of evaporated water are balanced, and the electrodeposited polypyrrole has good light absorption.

[0100] 1. Evaporation rate test is a key parameter to describe the energy efficiency of the evaporator. The evaporation rate test is carried out according to the following steps: put the double-layer polypyrrole deposited nickel foam sodium alginate hydrogel solar evaporator into a beaker, add water, fill the empty water surface with PS foam, and test the light intensity at 1kw / m 2, the temperature is room temperature, the weight change of water is recorded every 5 minutes, and the evaporation rate (R) is calculated according to the formula.

[0101]

[0102] Where M: change in water mass (Kg);

[0103] S: Evaporator area (area of ​​electrodeposited polypyrrole nickel foam) (m 2 );

[0104] h: irradiation time (h).

[0105] 2. Determination of equivalent enthalpy of evaporator:

[0106] The evaporator was placed on the surface of pure water and then placed in a constant temperature and humidity chamber as the experimental group; the pure water with the same surface area as the evaporator was used as the control group and placed in a constant temperature and humidity chamber; the temperature was set to 22°C and the relative humidity was 45%, and the test was conducted under normal atmospheric pressure and dark environment, so as to ensure that the heat absorbed by the evaporator and pure water is consistent. After 6 hours of placement, the equivalent evaporation enthalpy of the evaporator (△Hequ, J / g) was calculated according to the formula.

[0107] △Hvap×m0=△Hvau×m1

[0108] Where △Hvap: enthalpy of evaporation of pure water at 25°C (2246 J / g);

[0109] m0: mass change of pure water (g);

[0110] m1: change in mass of water in the evaporator (g).

[0111] 3. Photothermal efficiency test:

[0112] Photothermal efficiency is an important indicator for evaluating evaporator performance. The photothermal efficiency (η) is calculated according to the formula.

[0113] η=R1×(△Hequ) / (q×Copt)

[0114] Where R1: relative evaporation rate (kgm -2 h -1 ), the evaporation rate (R) minus the dark evaporation rate of water;

[0115] △Hequ: Equivalent enthalpy of evaporation (jg -1 )

[0116] q: Density of sunlight (w / m 2 );

[0117] Copt: Optical concentration at the evaporator surface.

[0118] in Figure 7 and Figure 8 The evaporation rate test was conducted using natural seawater, which was taken from the Yellow Sea (Weihai, Shandong); Fig. 9 The evaporation rate test was conducted using a NaCl solution with a mass percentage of 3.5% to 25%; Fig.10 The evaporation rate test was carried out using a 25% by mass NaCl solution; Fig.11 Evaporation rate test was performed using 1 mol / L HCL solution or 1 mol / L NaOH solution;

[0119] When the solar intensity is 1kw / m 2 At room temperature, the evaporation rates of nickel foam immersed in half the thickness of the hydrogel (comparative experiment 1), not immersed in the hydrogel (comparative experiment 2), and completely immersed in the hydrogel (example 1) were compared. The seawater was taken from the Yellow Sea (Weihai, Shandong), which were 3.06Kg·m -2 ·h -1 , 2.83Kg·m -2 ·h -1 and 3.22Kg·m -2 ·h -1 It can be seen that the evaporator prepared by immersing the entire structure of nickel foam into hydrogel has the highest evaporation rate.

[0120] Figure 7 When the solar intensity is 1kw / m 2 The relationship between the evaporation rate, photothermal efficiency and the concentration change of calcium chloride in the sodium alginate hydrogel in step 2③ of the double-layer polypyrrole deposited nickel foam solar evaporator prepared in Examples 1 to 5 under room temperature conditions. The calcium ions in the calcium chloride will exchange with the sodium ions in the sodium alginate to form cross-linked bonds between the calcium ions and the sodium alginate molecules. These cross-linked bonds connect the sodium alginate molecules together to form a three-dimensional network structure. Increasing the amount of calcium chloride can enhance the strength of the hydrogel, but it will reduce the pore structure and affect the water transport effect. The evaporation rate was measured and it was found that the 0.07wt% CaCl solution still had a considerable evaporation rate with a good gel effect, and the evaporation rate was 3.22Kg·m -2 ·h -1 , the photothermal efficiency is 91.8%.

[0121] Figure 8 When the solar intensity is 1kw / m 2The relationship between the evaporation rate, photothermal efficiency and hydrogel thickness of the double-layer polypyrrole deposited nickel foam sodium alginate hydrogel solar evaporator prepared in Examples 3, 6 to 9 under room temperature conditions. The thickness of the hydrogel in the evaporator affects the water transfer rate. The thicker the thickness, the greater the force required for water transfer. However, the thickness of the hydrogel has a certain insulation effect on the photothermal interface, reducing heat loss in the evaporation system. It was measured that 2 cm thickness is the appropriate thickness of the sodium alginate hydrogel in the evaporation system, and the evaporation rate is 3.22 kg·m -2 ·h -1 , the photothermal efficiency is 91.8%.

[0122] Fig. 9 When the solar intensity is 1kw / m 2 The evaporation rate of the double-layer polypyrrole deposited nickel foam sodium alginate hydrogel solar evaporator prepared in Example 1 in different concentrations of NaCl solution for 8 hours under room temperature conditions. As can be seen from the figure, the water evaporation experiment was carried out for 8 hours in different salinity solutions with a mass percentage of 3.5% to 25%. In the salinity solutions with a mass percentage of 3.5%, 7%, 10.5% and 15%, the stable evaporation rates were 3.22Kg·m -2 ·h -1 、3.18Kg·m -2 ·h -1 、3.15Kg·m -2 ·h -1 3.09Kg·m -2 ·h -1 In the 20% and 25% brine, the evaporation rate is slightly reduced, but still reaches 2.94Kg·m -2 ·h -1 and 2.83Kg·m -2 ·h -1 , indicating that the evaporator has good salt resistance.

[0123] Fig.10 When the solar intensity is 1kw / m 2 The evaporation rate variation diagram of the double-layer polypyrrole electrodeposited nickel foam sodium alginate hydrogel solar evaporator prepared in Example 1 was repeatedly evaporated in 25% NaCl solution for 7 days under room temperature conditions. The evaporation was 8 hours per day, and the results showed that the evaporator had good stability and reusability in high-concentration NaCl solution.

[0124] Fig.11 When the solar intensity is 1kw / m 2The pH test paper comparison diagram of 1mol / LHCL and 1mol / LNaOH solutions before and after evaporation using the double-layer polypyrrole deposited nickel foam sodium alginate hydrogel solar evaporator prepared in Example 1 under room temperature conditions; the pH value of the solution before and after evaporation was detected by pH test paper. The pH value of 1mol / L HCl solution after evaporation was about 6.0, and the pH value of 1mol / LNaOH solution after evaporation was about 7, which was close to neutral after evaporation purification, proving that the evaporator has a good purification effect on strong acid and strong base solutions.

[0125] Fig.12 This is a physical picture of the double-layer polypyrrole deposited nickel foam sodium alginate hydrogel solar evaporator prepared in Example 1.

Claims

1. A method for preparing a double-layer polypyrrole deposited nickel foam sodium alginate hydrogel solar evaporator, characterized in that It is carried out in the following steps:

1. Preparation of nickel foam light-absorbing layer of electrodeposited polypyrrole: ① washing and drying the nickel foam to obtain pretreated nickel foam; ② mixing pyrrole, acetonitrile and tetrabutylammonium tetrafluoroborate to obtain a mixed solution of pyrrole, acetonitrile and tetrabutylammonium tetrafluoroborate; ③ Using the pretreated nickel foam as the working electrode, the copper sheet as the counter electrode, silver chloride as the reference electrode, and the mixed solution of pyrrole, acetonitrile and tetrabutylammonium tetrafluoroborate as the electrodeposition solution, the electrochemical workstation uses the chronoamperometry method, and the electrodeposition is performed for 1000s to 2000s at a voltage of 1V to 4V and a temperature of 20°C to 50°C. After deposition, the nickel foam light-absorbing layer of the electrodeposited polypyrrole is washed and dried.

2. Preparation of sodium alginate hydrogel: ① Add sodium alginate into distilled water to obtain a sodium alginate solution; ② Add calcium chloride to distilled water to obtain a calcium chloride solution; ③ Adding calcium chloride solution into sodium alginate solution and heating to dissolve to obtain sodium alginate hydrogel; 3. Combining water absorption layer and light absorption layer to prepare solar seawater evaporation system: The electro-deposited polypyrrole nickel foam light-absorbing layer is placed at the bottom of a container, and the sodium alginate hydrogel is poured into the container from the surface of the electro-deposited polypyrrole nickel foam light-absorbing layer to form a hydrogel layer on the upper surface of the electro-deposited polypyrrole nickel foam light-absorbing layer, and then the container is allowed to stand for one time at room temperature until bubbles in the hydrogel are discharged, and a calcium chloride solution is added to the hydrogel layer along the inner wall of the container, and then the container is allowed to stand for a second time at room temperature, and the sample is taken out and soaked in distilled water, and finally the excess hydrogel is removed to obtain a double-layer polypyrrole deposited nickel foam sodium alginate hydrogel solar evaporator; The double-layer polypyrrole deposited nickel foam and sodium alginate hydrogel solar evaporator is a top-bottom structure, the nickel foam of the electrodeposited polypyrrole is a light absorbing layer, and the sodium alginate hydrogel is a water absorbing layer.

2. The method for preparing a double-layer polypyrrole deposited nickel foam sodium alginate hydrogel solar evaporator according to claim 1, characterized in that The thickness of the nickel foam described in step 1① is 1 mm to 5 mm, and the porosity is 80% to 98%.

3. The preparation method of a double-layer polypyrrole deposited nickel foam sodium alginate hydrogel solar evaporator according to claim 1 is characterized in that The volume ratio of pyrrole to acetonitrile in step 1 ② is 1:(100-200); the mass ratio of the volume of pyrrole to tetrabutylammonium tetrafluoroborate in step 1 ② is 1 mL:(1-3) g.

4. The method for preparing a double-layer polypyrrole deposited nickel foam sodium alginate hydrogel solar evaporator according to claim 1, characterized in that The distance between the working electrode and the counter electrode described in step 1③ is 2cm to 3cm.

5. The method for preparing a double-layer polypyrrole deposited nickel foam sodium alginate hydrogel solar evaporator according to claim 1, characterized in that The mass percentage of the sodium alginate solution described in step 2① is 2.5% to 4.5%; the mass percentage of the calcium chloride solution described in step 2② is 0.15% to 0.30%.

6. The method for preparing a double-layer polypyrrole deposited nickel foam sodium alginate hydrogel solar evaporator according to claim 1, characterized in that The volume ratio of the calcium chloride solution to the sodium alginate solution described in step 2③ is 1:(1.5-3).

7. The method for preparing a double-layer polypyrrole deposited nickel foam sodium alginate hydrogel solar evaporator according to claim 1, characterized in that The heating and dissolving described in step 2③ is specifically heating at a temperature of 80°C to 90°C for 45min to 90min.

8. The method for preparing a double-layer polypyrrole deposited nickel foam sodium alginate hydrogel solar evaporator according to claim 1, characterized in that In step 3, the mixture is allowed to stand at room temperature for 0.5 h to 1.5 h once; in step 3, the mixture is allowed to stand at room temperature for 15 h to 24 h twice; in step 3, the mixture is soaked in distilled water at room temperature for 4 h to 12 h.

9. The method for preparing a double-layer polypyrrole deposited nickel foam sodium alginate hydrogel solar evaporator according to claim 1, characterized in that In step 3, a hydrogel layer with a thickness of 1 cm to 3 cm is formed on the upper surface of the electro-deposited polypyrrole nickel foam light-absorbing layer; the mass percentage of the calcium chloride solution in step 3 is 0.05% to 0.1%.

10. The method for preparing a double-layer polypyrrole deposited nickel foam sodium alginate hydrogel solar evaporator according to claim 1, characterized in that The volume ratio of the calcium chloride solution described in step 3 to the sodium alginate hydrogel added to the container is 1:(0.5-2).

Citation Information

Patent Citations

  • Photothermal evaporation system with self-desalting surface and preparation method thereof

    CN109422317A

  • Hydrogel evaporation film, preparation method and applications thereof

    CN111170392A

  • Solar water evaporation material

    CN113149114A

  • Preparation and use method of functionalized suspended filter material

    CN115259404A

  • Efficient photo-thermal conversion photo-thermal layer, preparation method thereof and evaporator

    CN116479656A

Cited By

  • Flexible polypyrrole modified enteromorpha thermophotovoltaic film, preparation method and application thereof

    CN120535053B

  • Hydrogel and foam framework material composite interface evaporator and preparation method thereof

    CN120646944A

  • A hydrogel and foam skeleton material composite interface evaporator and a preparation method thereof

    CN120646944B